Architected functionally graded porous lattice structures for optimized elastic-plastic behavior. (August 2020) - Mahbod, Mahshid; Asgari, Masoud; Mittelstedt, Christian
In this paper, the elastic–plastic mechanical properties of regular and functionally graded additively manufactured porous structures made by a double pyramid dodecahedron unit cell are investigated. The elastic moduli and also energy absorption are evaluated via finite element analysis. Experimental compression tests are performed which demonstrated the accuracy of numerical simulations. Next, single and multi-objective optimizations are performed in order to propose optimized structural designs. Surrogated models are developed for both elastic and plastic mechanical properties. The results show that elastic moduli and the plastic behavior of the lattice structures are considerably affected by the cell geometry and relative density of layers. Consequently, the optimization leads to a significantly better performance of both regular and functionally graded porous structures. The optimization of regular lattice structures leads to great improvement in both elastic and plastic properties. Specific energy absorption, maximum stress, and the elastic moduli in x - and y -directions are improved by 24%, 79%, 56%, and 9%, respectively, compared to the base model. In addition, in the functionally graded optimized models, specific energy absorption and normalized maximum stress are improved by 64% and 56%, respectively, in comparison with the base models.